Meninjau Ulang Landasan Normatif Perbankan Syariah di Indonesia - Fathurrahman, Ayief (Al-Mawarid Jurnal Hukum Islam, 2010)
In this article. the writer tries to describe the reality of classical fiqh which has been becoming the normative foundation of Islamic banking operations. The evidence suggests that classical fiqh has got difficulties and inability to respond the contemporary problems, particularly the banking shariâah problems. Therefore, it is required a new formulation of dynamic fiqh in accordance with the times and able to respond contemporary problems. Therefore, it is urgent need to reconstruct the normative foundation of Shariâah banking in Indonesia, especially that of the classical Islamic jurisprudence.